A Practical Geotechnical Analysis of in situ Stress Variations and Hydraulic Stability of Small Weirs Using SEEP/W and SIGMA/W Simulation - Al Siaede, Riaed S. (Iraqi Journal of Science, 2019)
Geotechnical soil problems underneath foundation of hydraulic structures occurs due to engineering soil properties, geological setting and hydraulic properties of the projects. Two finite element programs of Geoslope 2012 software, SIGMA/W and SEEP/W, were used for analysis of in situ stresses, load deformation behavior, seepage quantity and vertical gradient below Teeb weir foundation, to compute factors of safety against seepage uplift. The site soil is a granular (gravel, sand and silt), weakly cemented soil cohered by gypsum and clay materials. The area has low lying topography, with slightly tectonic activities. The model results show that the upstream side stresses are reduced while the pore pressure are increased, indicating decreased stability. Soil displacement and settlement were measured and the effects of these displacements on the low cemented soil particles were discussed. The pressure distribution and vertical hydraulic gradient measured and used for analyze the weir stability. Finally, the soil potential failure zones were drawn to fix the main risks in each sides of the weir.